A Case Study of Leukemic Retinopathy - Bhattarai, Sabina; Paudel, Monika; Shrestha, Anju (Journal of Bharatpur Hospital, 2025)
This case report presents an 8-year-old male with a prior diagnosis of acute lymphoblastic leukemia, presenting with blurred vision in both eyes following chemotherapy. Ophthalmic evaluation revealed a visual acuity of 6/9P in both eyes, alongside clinical features consistent with leukemic retinopathy. Findings included bilateral intraretinal hemorrhages and subhyaloid hemorrhages. Leukemic retinopathy, an uncommon ocular complication of leukemia, typically results from leukemic cell infiltration into retinal tissues and is most frequently associated with acute forms of the disease. It can also be a consequence of leukemia-induced hematologic abnormalities, which manifest as intraretinal hemorrhages (dot-blot hemorrhages, flame hemorrhages, Roth spots), preretinal hemorrhages, and cotton-wool spots. These ocular manifestations may signal systemic disease progression and are prognostic indicators, underscoring the importance of timely interdisciplinary management.